X = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 2 − 1 2 2 7 4 2 4 5 − 6 1 2 2 3 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣
Find the value of det ( X ) .
If you don't know how to expand determinants, look at this wiki
Note: This problem isn't orginal.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I am sorry for not mentioning the origin of the problem but I was deliberate to take the problem from khan academy because those who don't know how to solve 4 × 4 determinant understand the example well when they see the same problem is solved in the video , and the problem is just a practice for this NOTE
Log in to reply
Should at least mention the problem is not original.
Log in to reply
Sir,can I use your solution in my new Wiki ?
Sir, is it necessary that any 4 × 4 can be expressed as an upper (or lower) triangular matrix ?
My solution is by Expansion of Minors. I considered the first column. d e t X = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ 1 1 2 − 1 2 2 7 4 2 4 5 − 6 1 2 2 3 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = 1 ∣ ∣ ∣ ∣ ∣ ∣ 2 7 4 4 5 − 6 2 2 3 2 7 4 4 5 − 6 ∣ ∣ ∣ ∣ ∣ ∣ − 1 ∣ ∣ ∣ ∣ ∣ ∣ 2 7 4 2 5 − 6 1 2 3 2 7 4 2 5 − 6 ∣ ∣ ∣ ∣ ∣ ∣ + 2 ∣ ∣ ∣ ∣ ∣ ∣ 2 2 4 2 4 − 6 1 2 3 2 2 4 2 4 − 6 ∣ ∣ ∣ ∣ ∣ ∣ + 1 ∣ ∣ ∣ ∣ ∣ ∣ 2 2 7 2 4 5 1 2 2 2 2 7 2 4 5 ∣ ∣ ∣ ∣ ∣ ∣
= 1 [ 3 0 + 3 2 − 8 4 − ( 4 0 − 2 4 + 8 4 ) ] − 1 [ 3 0 + 1 6 − 4 2 − ( 2 0 − 2 4 + 4 2 ) ] + 2 [ 2 4 + 1 6 − 1 2 − ( 1 6 − 2 4 + 1 2 ) ] + 1 [ 1 6 + 2 8 + 1 0 − ( 2 8 + 2 0 + 8 ) ]
= − 1 2 2 + 3 4 + 4 8 − 2
= − 4 2
Problem Loading...
Note Loading...
Set Loading...
After solving the problem, I noticed that the problem solution to this problem is given by this video clip from Khan Academy. Abdulrahman Khaled should give credit the originator of the problem and mentioned that the problem is not original.
Anyway, as mentioned in the video, the easy way to solve this to make the matrix into either an upper or lower triangular matrix with row operations and then the determinant is given by the product of the diagonal elements. Two row operation rules are involved.
I am showing another way of applying the same method here.
[ X ] = ⎣ ⎢ ⎢ ⎡ 1 1 2 − 1 2 2 7 4 2 4 5 − 6 1 2 2 3 ⎦ ⎥ ⎥ ⎤
r o w 1 → r o w 1 r o w 2 − 2 r o w 1 → r o w 2 r o w 3 − 2 r o w 1 → r o w 3 r o w 4 − 3 r o w 1 → r o w 4 ⇒ ⎣ ⎢ ⎢ ⎡ 1 − 1 0 − 4 2 − 2 3 − 2 2 0 1 − 1 2 1 0 0 0 ⎦ ⎥ ⎥ ⎤
r o w 1 → r o w 1 r o w 2 → r o w 2 r o w 3 → r o w 3 r o w 4 + 1 2 r o w 3 → r o w 4 ⇒ ⎣ ⎢ ⎢ ⎡ 1 − 1 0 − 4 2 − 2 3 3 4 2 0 1 0 1 0 0 0 ⎦ ⎥ ⎥ ⎤
r o w 1 → r o w 1 r o w 2 → r o w 2 r o w 3 → r o w 3 r o w 4 + 1 7 r o w 2 → r o w 4 ⇒ ⎣ ⎢ ⎢ ⎡ 1 − 1 0 − 2 1 2 − 2 3 0 2 0 1 0 1 0 0 0 ⎦ ⎥ ⎥ ⎤
r o w 4 → r o w 1 r o w 2 → r o w 2 r o w 3 → r o w 3 r o w 1 → r o w 4 ⇒ − ⎣ ⎢ ⎢ ⎡ − 2 1 − 1 0 1 0 − 2 3 2 0 0 1 2 0 0 0 1 ⎦ ⎥ ⎥ ⎤
Therefore, det [ X ] = X = − ( − 2 1 ) ( − 2 ) ( 1 ) ( 1 ) = − 4 2